Destructive Spondyloarthropathy in Patients on Long‐Term Peritoneal Dialysis or Hemodialysis. Issue 4 (7th April 2015) - Hayami, Noriko; Hoshino, Junichi; Suwabe, Tastuya; Sumida, Keiichi; Mise, Koki; Hamanoue, Satoshi; Sawa, Naoki; Kitajima, Izuru; Hirota, Yutaka; Oohashi, Kenichi; Fujii, Takeshi; Okuda, Itsuko; et al.
Abstract Destructive spondyloarthropathy (DSA) is the most serious spinal complication of dialysis‐related amyloidosis in patients on long‐term hemodialysis (HD), but we could not find any information about DSA in patients on peritoneal dialysis (PD) for over 10 years. We retrospectively evaluated factors contributing to DSA in HD and PD patients. Sixty‐seven patients on dialysis for 10 to 19 years were compared between a PD group (n = 23) or a HD group (n = 44). In the PD group, nine patients (39%) developed DSA. The mean age of DSA patients was significantly higher than that of non‐DSA patients (66.2 ± 10.0 vs. 51.0 ± 12.8 years, P = 0.03). The frequency of cervical spine DSA did not show any difference between the PD and HD groups, but the frequency of lumbar spine DSA showed a significant difference (22% vs. 5%, P = 0.04). The serum beta‐2 microglobulin (B2MG) level was significantly higher in PD patients than in HD patients (38.4 mg/L vs. 27.4 mg/L, P = 0.0025). Mechanical stress such as elevation of the intra‐abdominal pressure due to infusion of PD fluid (1500 mL to 2000 mL) for over 10 years might contribute to lumbar DSA in patients on long‐term PD.